An Experimental and Numerical Investigation of Performance of Nanofluids - Gupta, Richa (My University, 2017)
Literature report shows that nanofluids have potential to perform as effective coolants as compared to the conventional coolants. This unique feature of nanofluids is due to their improved thermo physical properties. The thermal conductivity is one of them which has comparatively more significance. A significant amount of work has been also reported by various researchers on the thermal conductivity enhancement of nanofluids. There are many static as well as dynamic models which have been suggested to measure the thermal conductivity of variety of nanofluids. In addition to the fundamental studies about such variety of models, a very limited work has been reported about the numerical investigation of performance of such nanofluids. In the present work, an attempt has been made to investigate into the behavior of a particular type of flow of nanofluid on a vertical flat plate. The problem has been well formulated by imposing the suitable boundary conditions. Subsequently to this, fundamental governing equation have been written using the properties of nanofluid for the flow of nanofluid along the vertical plate. In this arrangement, the general governing equations for the flow over a flat plate and thermo physical property equations about the performance of nanofluids have been coupled together. All the equations are solved together to obtain the final partial differential equations. These equations are expressed in term of transformed coordinates. The resulting non-linear partial differential equations were solved using finite element method with the help of MATLAB. The temperature distribution across the vertical plate has been investigated and plotted. The results seem to follow the expected variations. In second part of the work, the thermal conductivity of Al2O3-H2O nanofluid has been investigated against volume fraction of nanoparticles into base fluid and temperature rise. A thermal property analyzer (KD2 Pro) has been used to measure the thermal conductivity of different samples nanofluid. The experimentation has been conducted only up to 60°C. The results obtained have been compared with some of the fundamental models. From the experimental results, it was observed that the thermal conductivity ratio, Knf /Kf increases with increase in temperature as well as with volume fraction (0.01 to 0.08).
Keywords: Thermal conductivity; nanofluid; numerical study; experimental study; KD2 pro